The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/17470210802373035
|View full text |Cite
|
Sign up to set email alerts
|

Category length produces an inverted-U discriminability function in episodic recognition memory

Abstract: Four experiments used signal detection analyses to assess recognition memory for lists of words consisting of differing numbers of exemplars from different semantic categories. The results showed that recognition memory performance, measured by d(a), (a) increased as category length (CL, the number of study-list items selected from the same semantic category) increased from 1 to 8 but then decreased as CL further increased from 8 to 14, (b) was greater when 2 studied items from the same category occurred back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 50 publications
3
27
1
Order By: Relevance
“…In category length (CL) designs, the increase in the false alarm rate (FAR) with increasing CL is robust across a wide range of studies (e.g., Cho & Neely, 2013;Criss & Shiffrin, 2004;Dennis & Chapman, 2010;Neely & Tse, 2009;Robinson & Roediger, 1997;Shiffrin et al, 1995). The effects on the hit rate (HR) are somewhat less consistent.…”
Section: Similarity Effects In Global Matching Modelsmentioning
confidence: 99%
“…In category length (CL) designs, the increase in the false alarm rate (FAR) with increasing CL is robust across a wide range of studies (e.g., Cho & Neely, 2013;Criss & Shiffrin, 2004;Dennis & Chapman, 2010;Neely & Tse, 2009;Robinson & Roediger, 1997;Shiffrin et al, 1995). The effects on the hit rate (HR) are somewhat less consistent.…”
Section: Similarity Effects In Global Matching Modelsmentioning
confidence: 99%
“…Al though controlled studies have found no effect of category length using taxonomic categories (Cho & Neely, 2013;Neely & Tse, 2009), Maguire et al (2010) found a large effect of large effect of category length on 2AFC performance for associative categories while finding no effect of category length when taxonomic cate gories are used. Similarly, the studies that have found DRM effects, which are possibly the biggest false memory effects found in list memory paradigms, often use associatively related catego ries (Robinson & Roediger, 1997;Roediger & McDermott, 1995).…”
Section: Arguments For Item Noise Modelsmentioning
confidence: 99%
“…In contrast, item-noise models predict interference from other items, especially from related items. For instance, category-length manipulations affect recognition (Criss & Shiffrin, 2004;cf, Dennis & Chapman, 2010;Neely & Tse, 2009;Shiffrin, Huber, & Marinelli, 1995) and varying the proportion of high-frequency versus low-frequency words on a study list affects recognition accuracy (Dorfman & Glanzer, 1988;Malmberg & Murnane, 2002).…”
Section: Prior Tests Of the Modelsmentioning
confidence: 99%